PENGEMBANGAN SUMBER DAYA MANUSIA DI KANTOR KECAMATAN SERASAN TIMUR KABUPATEN NATUNA - E.21111112, Odira (FISIP Universitas Tanjungpura, 2013)
The writing of this article aims to determine the development of human resources at the District Office Serasan East Natuna. This study included in the descriptive study with a qualitative analysis focusing on the variable employee training, employee education and development of employees. Results of research in the field suggests that the training has not been followed by all personnel in the District Office East Natuna regency Serasan reason is because there is no opportunity given by the government as well as budget constraints Natuna regency, the level of education in the District Office was still low and there are difficulties in the development of human resources.Â Keywords: Employee Training, Employee Education and Development Employee